Correlations between Serum Interleukin-4 with Pro- and Anti-inflammatory Markers in Type 1 and 2 Diabetes: A Comparative Study - M.I. Dezayee, Zhian (Zanco Journal of Medical Sciences (ZJMS), 2025)
Background and objective: Interleukin-4 inhibits the secretion of many inflammatory cytokines and it acts as anti-inflammatory against insulinits that induced by autoimmunity in type-1 diabetes. This cross-sectional study aimed to determine the serum level IL-4 in patients with T1D and T2D, and to look into its relation to other pro-and anti- inflammatory cytokines and glycemic status. Methods: Patients with a history of type-1 (T1D) (Group I, n=75) and type-2 (T2D) diabetes (Group II, n=75) were recruited from the Center of Diabetes in Erbil. Glycemic indices (included fasting serum glucose, insulin, glycated hemoglobin, c- peptide) and inflammatory-related cytokines (including highly sensitive C-reactive protein [hs-CRP], IL-1β, IL-4, IL-10, Interferon [INF-γ], and tumor necrosis factor [TNF-α]) were measured. Results: Group II patients showed significant increase of hs-CRP, IL-10, and IL-4, while the serum levels of IL-1β and INF-γ were significantly reduced compared with Group I. Significant inverse correlations between IL-4 with each of the following markers; hs-CRP (r=-0.858), IL-1β(r=-0.890), INF-γ(r=-0.859), IL-10(-0.685), and TNF-α (r=-0.733) with predictive values ranged between 46.9% and 73.8% were observed in the Group II but not in the Group I. Non-significant correlation between IL-4 and glycemic indices were observed in Group I and II. Conclusion: We conclude that determination of IL-4 can help to discriminate between autoimmune-from inflammatory markers that are associated with diabetes, and can serve as a predictor cytokine in T2D.